2021
DOI: 10.3390/ijms22031407
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA CASC19 Contributes to Radioresistance of Nasopharyngeal Carcinoma by Promoting Autophagy via AMPK-mTOR Pathway

Abstract: Nasopharyngeal carcinoma (NPC) is one of the most frequent head and neck malignant tumors and is majorly treated by radiotherapy. However, radiation resistance remains a serious obstacle to the successful treatment of NPC. The aim of this study was to discover the underlying mechanism of radioresistance and to elucidate novel genes that may play important roles in the regulation of NPC radiosensitivity. By using RNA-seq analysis of NPC cell line CNE2 and its radioresistant cell line CNE2R, lncRNA CASC19 was sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…In the present study, our constructed risk signature consisted of four lncRNAs which were closely related to NSCLC prognosis. Among these five lncRNAs, CASC19 related AMPK-mTOR pathway [46]. In addition, CASC19 also has an oncogenic effect on NSCLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, our constructed risk signature consisted of four lncRNAs which were closely related to NSCLC prognosis. Among these five lncRNAs, CASC19 related AMPK-mTOR pathway [46]. In addition, CASC19 also has an oncogenic effect on NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer (PC), CASC19 could facilitate malignant growth and metastasis of PC via miR-148b/E2F7 ceRNA axis with sponge activity [ 45 ]. As suggested by Liu et al, CASC19 was highly expressed in radioresistant nasopharyngeal carcinoma (NPC) cells and could confer radioresistance in NPC through autophagy-related AMPK-mTOR pathway [ 46 ]. In addition, CASC19 also has an oncogenic effect on NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA CASC19 was widely reported and markedly upregulated in multiple tumor tissues and cells, higher CASC19 expression is associated with tumor progression and poorer prognoses, including colorectal cancer, advanced gastric cancer, non-small lung cancer cells, and pancreatic cancer [32][33][34][35]. Two other studies revealed that a high expression level of CASC19 was positively correlated with radio resistance in cervical cancer and nasopharyngeal carcinoma [36,37]. However, the other seven prognostic EMT-related lncRNAs (AC103760.…”
Section: Discussionmentioning
confidence: 99%
“…In LSCC, GAS5 inhibited the viability of AMC-HN-8 cells and induced apoptosis, acting as a tumor suppressor by regulating the miR-26a-5o/ULK2 axis ( 130 ). Conversely, CASC19 suppressed cellular autophagy by inhibiting the AMPK/mTOR pathway, contributing to the radioresistance of NPC by regulating autophagy ( 114 ).…”
Section: Lncrnas In Drug Resistance Mechanismsmentioning
confidence: 99%